KAJIAN PENGEMBANGAN KAWASAN CAMPURAN (MIXED USE) DI PERKOTAAN - Medtry MEDTRY (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2021)
Abstract A mixed use area is basically an urban area that is designed in an integrated manner (integrated development), with a fairly high building density and a combination of land functions that are mixed (mixed used), where the most important key to its success is the functioning of the control mechanism which is the implementation. from the regulations for the development of the superblock area itself (Wikipedia, 2018). Another definition based on arsitag.com states that Mixed use is the use of a building, a building complex, or an environment for more than one use. This concept has been adopted by several countries in the world since 1920. The idea is to combine offices, residences, and other activity centers in adjacent areas or even in the same building. In Indonesia, mixed areas are permitted and regulated in Government Regulation Number 15 of 2010 concerning Spatial Planning, which mandates that to improve the quality of spatial structures and spatial patterns. In addition, in the Regulation of the Minister of ATR / BPN Number 16 of 2017 concerning Guidelines for the Development of Transit Oriented Areas, Regulation of the Minister of ATR / BPN Number 1 of 2018 concerning the Compilation of Regional Spatial Planning (RTRW), and Regulation of the Minister of ATR / BPN Number 16 of 2018 concerning Compilation Detailed Spatial Planning (RDTR) and Zoning Regulations (PZ. In the spatial planning regulations, the mixed area is regulated in a mixed zone (C), which includes; housing and trade / services, housing and offices, trade / services and offices. For the use of the mixed zone category, it must be supported by the existence of a clear zone boundary which can limit the further expansion of the mixed function and there must be an effort to encourage the development of the mixed function towards a certain designated zone. Therefore, it is necessary to conduct this research to provide input and suggestions for related parties, including mixed area typology, mixed area prerequisites, mixed area principles, mixed area criteria and standards. Keywords: mixed-use area, typology, prerequisites, principles, criteria